PENGARUH GAYA KEPEMIMPINAN DAN LINGKUNGAN KERJA NON FISIK TERHADAP PRODUKTIVITAS KERJA PEGAWAI PADA BADAN KEPEGAWAIAN DAERAH KABUPATEN INDRAMAYU : Study Persepsional Pegawai - Mahfudin, - (2011)
Badan Kepegawaian Daerah Kabupaten Indramayu is a job-supporting element of Local Governments in the area of local civil service. Based on Target Achievement Measurement (Pengukuran Pencapaian Sasaran/PPS) in Fiscal Years of 2008 and 2009, a decreased number of employee working productivities occured. This was true because the leadership style and the non-physical workplace was ineffective. From this issue, a reseach of influence of leadership style and non-physical workplace on employee working productivity was conducted in Badan Kepegawaian Daerah Kabupaten Indramayu. It involved two independent variables and one dependent variable. The first independent variable (X1) is leadership style, and the second one (X2) is non-physical workplace and the dependent variable (Y) is employee working productivity. This investigation was descriptive and verificative, using explanatory survey method. The number of population in this study was 59 employees, where sampling technique was simple random sampling and the size was 51 employees. Data used was ordinal and interval, using coefficient correlation of Pearson product moment, and double linear regression analysis using coefficient determination (r square). Hypothesis test uses F-test to simultaneously identify the influence and t-test to partially identify. The findings show that the Leadership Style and Non-Physical Workplace have positive influence on the employee working productivity of Badan Kepegawaian daerah kabupaten Indramayu. The amount of this influence is 34.0% and the rest 66.0% is influenced by other factors that were not investigated.